MAKNA ASOSIATIF DALAM ANTOLOGI PUISI 길 (GIL) KARYA YUN DONG JU: SEBUAH KAJIAN SEMANTIK - Irbah, Hasna Dhia; Hardini, Tri Indri; Ansas, Velayeti Nurfitriana (Fakultas Ilmu Budaya, Universitas Mulawarman, 2020)
Research related to the associative meaning contained in the poem '길 (Gil)' in the anthology of poetry and prose by Yun Dong Ju aims to determine the types of associative meanings and meanings contained in one of Yun Dong Ju's poems. The meaning contained in words, phrases, or sentences in poetry can be in the form of meanings associated with something outside the language. Through the study of associative meanings, the meaning of words, phrases or sentences can be known from another point of view. In this research, the method used in this research is descriptive qualitative method. After the analysis process, the writer found 4 connotative meaning data, 6 affective meaning data, 1 reflective meaning data, and 1 collocative meaning data. The most common meaning found in this study is affective meaning. This shows that in the poetry that has been analyzed, many poets use words, phrases or sentences to express the feelings experienced during the Japanese colonial period in Korea.